2010
DOI: 10.1111/j.1600-0714.2009.00816.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunohistochemical analysis of P53and bcl-2 in benign and malignant salivary glands tumors

Abstract: Pleomorphic adenoma (PA) showed negative expression of P(53) and bcl-2 in 70% of cases, whereas all malignant salivary glands tumors were positive for P(53) and bcl-2. P(53) positive/bcl-2 positive immunostaining reaction was week in small size PA and was totally absent in larger lesions. However, all malignant tumors expressed P(53), with the highest record in low-grade adenocarcinoma (76%) and the lowest score was observed in both low-grade carcinoma in PA and adenocystic carcinoma. bcl-2 immunostaining was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

2
10
0

Year Published

2012
2012
2019
2019

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(12 citation statements)
references
References 37 publications
2
10
0
Order By: Relevance
“…This is in agreement with the results of Röijer et al (1997) and Al-Rawi et al (2010), who reported moderate p53 staining in their studied cases of ACC and correlated the associated immunoreactivity to the large size of the tumor, high grade, and extent of invasion. This is in agreement with the results of Röijer et al (1997) and Al-Rawi et al (2010), who reported moderate p53 staining in their studied cases of ACC and correlated the associated immunoreactivity to the large size of the tumor, high grade, and extent of invasion.…”
Section: Discussionsupporting
confidence: 93%
“…This is in agreement with the results of Röijer et al (1997) and Al-Rawi et al (2010), who reported moderate p53 staining in their studied cases of ACC and correlated the associated immunoreactivity to the large size of the tumor, high grade, and extent of invasion. This is in agreement with the results of Röijer et al (1997) and Al-Rawi et al (2010), who reported moderate p53 staining in their studied cases of ACC and correlated the associated immunoreactivity to the large size of the tumor, high grade, and extent of invasion.…”
Section: Discussionsupporting
confidence: 93%
“…13 Several biomarkers have been studied for their possible role as prognostic indicators of ACC in the lacrimal and salivary glands and as potential targets of molecular therapy. [14][15][16][17][18][19][20][21][22][23][24] No validated protocols exist for ACC of the lacrimal glands.…”
Section: Introductionmentioning
confidence: 99%
“…Positive p53 immunohistochemistry has been identified not only in malignant salivary gland tumors but also in tumors showing classic pleomorphic adenoma histology, cellular pleomorphic adenomas, and recurrent pleomorphic adenomas. [21][22][23] More significant is the utility of the nuclear antigen K i -67 as a predictor of tumor behavior, in malignant tumors a high proliferation rate is suggestive of more aggressive behavior. 24 The low proliferation rate in addition to classic pleomorphic adenoma histology with no evidence of malignant transformation of either cellular or stromal components definitively placed this tumor into the category of a recurrent pleomorphic adenoma.…”
Section: Discussionmentioning
confidence: 99%